2012
DOI: 10.1007/s10661-012-2573-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus sorption–desorption behaviour of river bed sediments in the Abshineh river, Hamedan, Iran, related to their composition

Abstract: Phosphorus (P) sorption by sediments may play a vital role in buffering P concentration in the overlying water column. To characterize P sorption-desorption in the river bed sediments, 17 bed sediment samples collected from Abshineh river, in a semi arid region, Hamedan, western Iran were studied through a batch experiment and related to sediment composition. The sorbed fraction ranged from 4.4% to 5.4% and from 38.5% to 86.0% of sorption maxima when 20 and 1,500 mg P kg(-1), respectively, was added to the sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 63 publications
2
16
0
1
Order By: Relevance
“…The occurrence of well expressed eutrophication phenomena, specifically phytoplankton bloom in this case, may be treated as a consequence of intensified anthropogenic pressure, especially of increased discharge of municipal sewage directly to the lake in last years and draining the waste-waters to the ground in the alimentation zone of water sources feeding the Turkusowe Lake [7]. Obviously, the presence of CaCO 3 deposits at the bottom of the lake has been responsible for the sorption and binding of part of SRP as well as organic compounds from the reservoir of water [15][16][17]. Nevertheless, in the opinion of the authors of this paper, the presence of CaCO 3 at the bottom of lake basin does not automatically cause "by itself" the surface water to be resistant to eutrophication under conditions of permanent stratification of surface and near-bottom waters being maintained practically constantly.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of well expressed eutrophication phenomena, specifically phytoplankton bloom in this case, may be treated as a consequence of intensified anthropogenic pressure, especially of increased discharge of municipal sewage directly to the lake in last years and draining the waste-waters to the ground in the alimentation zone of water sources feeding the Turkusowe Lake [7]. Obviously, the presence of CaCO 3 deposits at the bottom of the lake has been responsible for the sorption and binding of part of SRP as well as organic compounds from the reservoir of water [15][16][17]. Nevertheless, in the opinion of the authors of this paper, the presence of CaCO 3 at the bottom of lake basin does not automatically cause "by itself" the surface water to be resistant to eutrophication under conditions of permanent stratification of surface and near-bottom waters being maintained practically constantly.…”
Section: Resultsmentioning
confidence: 99%
“…This caused a 15 % decrease in PHY con-centration when the water moved further downstream. Thus, SRP was most of the time fully assimilated by phytoplankton in summer, but phytoplankton was also subject to mortality and could partly be recycled to eventually constitute an autochthonous source of available P. Remineralization of autochthonous labile organic particulate P, known as part of the "microbial loop", is described in the literature of phytoplankton ecology (Reynolds, 2006;Li et al, 2014) and mostly identified in lakes, reservoirs or estuarine systems (Jossette et al, 1999;James and Larson, 2008;Song and Burgin, 2017) and rarely in rivers (Descy et al, 2002;Withers and Jarvie, 2008). On the one hand, bacteria compete with phytoplankton for SRP availability, and on the other hand, bacterial mineralization recycles P and supports phytoplankton growth.…”
Section: P Recycling Within the Mlrcmentioning
confidence: 99%
“…Higher EPC 0 means higher tendency of P release from sediment. For example, in the Abshineh river, EPC 0 values were higher in upstream sites than at the downstream ones, suggesting that sediments in upstream and downstream may act as source and sink of phosphorus, respectively (Jalali and Peikam 2013). The mean EPC 0 value in the rivers sediments was significantly higher than that in the lake sediments (P<0.01), in conjunction with the case of the CaCO 3~P content (P<0.01) (Table 1).…”
mentioning
confidence: 90%